Pakatan's 100-day plan unrealistic, say experts - Elis, Shuhada; Koi Kye, Lee; Roy See, Wei Zhi; Ranai, Maizatul (New Straits Times, 2011)
PETALING JAYA: Pakatan Rakyat’s 100-day plan is fraught with uncertainties and is ultimately not feasible, says Mercury Securities Sdn Bhd research head Edmund Tham.